Motor functions in rat hindlimb muscles following neonatal sciatic nerve crush - Vejsada, R; Hník, P; Navarrete, R; Palecek, J; Soukup, T; Borecka, U; Payne, R (Neuroscience, 1991)
The sciatic nerve was crushed in the right hindlimb in newborn (3-8 h old) rats. Two to four months later, electromyographic activity was recorded from both the control and reinnervated ankle extensor muscles soleus or lateral gastrocnemius and from the ankle flexor muscle tibialis anterior. Tonic postural activity was present in the extensor muscles on both sides during quiet stance. The control flexor muscles were usually silent in this situation, but the reinnervated flexors exhibited abnormal sustained activity. During locomotion, the control extensors were activated during the stance phase and their mean burst made up 61.5% of the step cycle. The control tibialis anterior muscle fired only during the swing phase, with the burst lasting 18.1% of the step cycle. In the reinnervated extensor muscles, the mean burst duration was decreased (46% of the cycle) but the basic locomotor pattern was not impaired. The reinnervated tibialis muscle, however, was activated abnormally, with one appropriate flexor burst during the swing phase and an "extensor-like" burst during the stance phase of the step. Reflex responses to stretch were weak or absent on the operated side. Histological examination showed that the reinnervated soleus and tibialis muscles were almost devoid of muscle spindles. The motor unit mean firing rates in the reinnervated soleus (22 imp/s) and lateral gastrocnemius (45 imp/s) matched those of the control muscles (25 and 42 imp/s, respectively). In contrast to the phasic, high-frequency firing (52-80 imp/s) in the control tibialis, the reinnervated tibialis motor units fired at significantly lower rates (22-56 imp/s).(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: rozdrcení nervu; svaly; novorozená zvířata; Animals; nervus ischiadicus; Female; Hindlimb; Sciatic Nerve; inbrední kmeny potkanů; ženské pohlaví; Reflex; Rest; pohybová aktivita; Animals, Newborn; nervosvalová vřeténka; Muscle Spindles; odpočinek; Rats, Inbred Strains; atrofie; Electromyography; zadní končetina; Male; Atrophy; Nerve Crush; krysa rodu Rattus; reflex; Muscles; Motor Activity; zvířata; mužské pohlaví; Rats; elektromyografie